(NrASSKAZY(B; s (N~ERNYE GOSTI(B: [(NpOWESTX(B] / s (N~ASTX (B2s - (NgULIA(B, (NgEORGIJs ((NmOSKWA(B: s (NhUDOVESTWENNAQ LITERATURA(B, s, 1987)
(NwO WTOROJ TOM WO[LI IZBRANNYE RASSKAZY (B(1950-1985), (NISTORI^ESKAQ POWESTX (B"(N~ERNYE GOSTI(B" (1950) (NI ROMAN (B"(NsKAZANIE OB oMARE hAJQME(B" (1973).s
(NsKAZANIE OB oMARE hAJQMEs
rus
Keywords: (NrASSKAZY(B, (NPOWESTIs; (NiSTORI^ESKIJ ROMANs